Information technology and open source: Applications for education, innovation, and sustainability : SEFM 2012 Satellite Events, InSuEdu, MoKMaSD, and OpenCert Thessaloniki, Greece, October 1-2, 2012 Revised Selected Papers - Persico, Donatella; Fernandes, Sara; Garcia-Perez, Alexeis; Katsaros, Panagiotis; Shaikh, Siraj Ahmed; Stamelos, Ioannis; Cerone, Antonio (Lecture Notes in Computer Science, 2014)
This book constitutes revised selected papers from the following SEFM 2012 satellite events: InSuEdu, the First International Symposium on Innovation and Sustainability in Education; MokMaSD, the First International Symposium on Modelling and Knowledge Management for Sustainable Development and Open Cert, the 6th International Workshop on Foundations and Techniques for Open Source Software Certification, held in Thessaloniki, Greece, in October 2012. The total of 14 regular papers and 7 short papers included in this volume were carefully reviewed and selected from 35 submissions. The papers cover the topics related to the use of Information and Communication Technology (ICT) and Open Source Software (OSS) as tools to foster and support Education, Innovation and Sustainability.